Inclusión de lactobacillus plantarum en la alimentación de cerdas gestantes y lactantes sobre el desempeño de la camada - Vera Vera, Víctor Isidro (2020)
In order to evaluate the effect of the Lactobacillus plantarum probiotic on feeding pregnant and lactating sows on litter performance, an investigation was conducted at a commercial farm located in the Betania Sector of Canton El Carmen, province of Manabí. The variables studied were: number of piglets per litter (NPL), litter weight at birth (LWB), at 15 days (LW15) and at weaning (LW), piglet weight at birth (PWB), piglet weight 15 days (LW15 ) and at weaning (WPW), daily weight gain (DWG), piglet mortality (% M), body condition (BC) of sow before delivery (BCBF) and at weaning (BCW), the relationship was also determined cost-benefit. Were used 12 primiparous sows with 90 days in gestation. The experimental design used was completely randomized with three treatments and four repetitions: T0: control, without probiotic application; T1: 20 mL of probiotic (109UFC/ml) per kg of food and T2: 40mL of probiot (1010UFC/mL) per kg of food. Data were processed by analysis of variance. The results indicate that the use of probiotics showed no significant differences (P> 0.05) for LWB, LW15, and PW15. Showing differences (P <0.05) by the non-parametric route for: LWB, LWW and PWW. The DWG did not show significant differences (P> 0.05), however, the average DWG was higher than the T0. The statistically variable mortality showed no significant differences (P> 0.05). The BC of the sow was the same before delivery and at weaning. The benefit-cost ratio shows profitability in the three treatments, with T0 being higher.